Pelaksanaan Fungsi Manajemen Sumber Daya Manusia Dalam Meningkatkan Mutu Pendidikan Islam - Ahmad Aziz Fanani (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2013)
Human resource management (HRM) is an existing management within an organization and is managed in such a way, so that their potential can be developed and can be utilized to achieve predetermined objectives of the organization. Human resource management (HRM) is part of the organizational management focusing on the elements of HR. So the human resource management (HRM) can be grouped into two functions, namely, managerial functions and operational functions. Regarding managerial functions include planning, organizing, directing, and pengendalaian. The function operasinal mencaup subject of procurement, training and development, compensation, integration, and maintenance.